Synthesis and Characterization of B4C-Based Multifunctional Nanoparticles for Boron Neutron Capture Therapy Applications - Demichelis, Maria Paola (2024)
Nanoparticles composed of inorganic boron-containing compounds represent a promis-ing candidate as 10B carriers for BNCT. This study focuses on the synthesis, characterization, and assessment of the biological activity of composite nanomaterials based on boron carbide (B4C).Boron carbide is a compelling alternative to borated molecules due to its high volumetric B content,prolonged retention in biological systems, and low toxicity. These attributes lead to a substantialaccumulation of B in tissues, eliminating the need for isotopically enriched compounds. In our approach, B4C nanoparticles were included in composite nanostructures with ultrasmall superpara-magnetic nanoparticles (SPIONs), coated with poly (acrylic acid), and further functionalized with the fluorophore DiI. The successful internalization of these nanoparticles in HeLa cells was confirmed, and a significant uptake of 10B was observed. Micro-distribution studies were conducted using intracellular neutron autoradiography, providing valuable insights into the spatial distribution of the nanoparticles within cells. These findings strongly indicate that the developed nanomaterials hold significant promise as effective carriers for 10B in BNCT, showcasing their potential for advancing cancer treatment methodologies.